2017
DOI: 10.3201/eid2310.170106
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide-Resistant Mycoplasma pneumoniae Infection, Japan, 2008–2015

Abstract: We evaluated isolates obtained from children with Mycoplasma pneumoniae infection throughout Japan during 2008–2015. The highest prevalence of macrolide-resistant M. pneumoniae was 81.6% in 2012, followed by 59.3% in 2014 and 43.6% in 2015. The prevalence of macrolide-resistant M. pneumoniae among children in Japan has decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 14 publications
1
61
0
Order By: Relevance
“…After collection, each swab was placed into 3 mL of Universal Viral Transport Medium (Becton, Dickinson and Company) for DNA extracts. Mycoplasma pneumonia DNA was detected by real‐time PCR targeting a conserved part of the gene encoding the P1 adhesin …”
Section: Participants and Methodsmentioning
confidence: 99%
“…After collection, each swab was placed into 3 mL of Universal Viral Transport Medium (Becton, Dickinson and Company) for DNA extracts. Mycoplasma pneumonia DNA was detected by real‐time PCR targeting a conserved part of the gene encoding the P1 adhesin …”
Section: Participants and Methodsmentioning
confidence: 99%
“…Although her symptoms got better with levofloxacin, we should have administered corticosteroid as a cellular immune suppressor with antibiotic treatment. We did not use macrolide first because the prevalence of macrolide‐resistant M. pneumoniae remains high in Japan . One study reported the prevalence of macrolide‐resistant M. pneumoniae in adult patients with CAP was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…We did not use macrolide first because the prevalence of macrolide-resistant M. pneumoniae remains high in Japan. 10 One study reported the prevalence of macrolideresistant M. pneumoniae in adult patients with CAP was 100%. The prevalence of azithromycin-resistant M. pneumoniae was reported 72%, and tuberculosis test was negative in this patient; thus, we chose levofloxacin instead of macrolide antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al15 reported a year‐by‐year variation in the prevalence of macrolide‐resistant M. pneumoniae in Japan, demonstrating an increase from 55.6% to 81.6% between 2008 and 2012, with a gradual decrease thereafter, reaching 43.6% by 2015. Despite this decrease, the macrolide resistance rate of M. pneumoniae remains high in Japan, and its clinical importance is unaltered.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The prevalence of macrolide-resistant M. pneumoniae is 23.3%-100% in East Asian regions, 3.5%-13.2% in North America, and below 10% in European countries, except Italy, which has a higher rate of 26%. 11 Tanaka et al 15…”
Section: Introductionmentioning
confidence: 99%